2001
DOI: 10.1080/j148v19n03_04
|View full text |Cite
|
Sign up to set email alerts
|

Post Discharge Use of Bathing Equipment Prescribed by Occupational Therapists

Abstract: Prescription of adaptive equipment is a core component of occupational therapy practice. Adaptive equipment can help people with physical limitations to optimize their independence during the completion of activities of daily living. In this paper, we report the results of an audit of patients' use of eight pieces of prescribed bathing equipment eight weeks after discharge from hospital, and analyze the reasons for their patterns of use. Participants were 64 patients (mean age = 70.7 years, 62.5% female), disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This study speaks of assistive devices, which includes adaptive and mobility aids such as a walker, cane, wheelchair, or crutches. Another study found that the patients' perceptions of the benefit of using pieces of adaptive equipment appear to influence compliance (Wielandt, McKenna, Tooth, & Strong, 2001). One study conducted an audit of past total hip replacement patients in order to determine the cost-effectiveness of providing hip packs.…”
Section: Literature Reviewmentioning
confidence: 97%
“…This study speaks of assistive devices, which includes adaptive and mobility aids such as a walker, cane, wheelchair, or crutches. Another study found that the patients' perceptions of the benefit of using pieces of adaptive equipment appear to influence compliance (Wielandt, McKenna, Tooth, & Strong, 2001). One study conducted an audit of past total hip replacement patients in order to determine the cost-effectiveness of providing hip packs.…”
Section: Literature Reviewmentioning
confidence: 97%